Predictive Value of Age- and Sex-Specific Nomograms of Global Plaque Burden on Coronary Computed Tomography Angiography for Major Cardiac Events. (March 2017) - Naoum, Christopher; Berman, Daniel S.; Ahmadi, Amir; Blanke, Philipp; Gransar, Heidi; Narula, Jagat; Shaw, Leslee J.; Kritharides, Leonard; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Budoff, Matthew J.; et al.
Abstract : Background—: Age-adjusted coronary artery disease (CAD) burden identified on coronary computed tomography angiography predicts major adverse cardiovascular event (MACE) risk; however, it seldom contributes to clinical decision making because of a lack of nomographic data. We aimed to develop clinically pragmatic age- and sex-specific nomograms of CAD burden using coronary computed tomography angiography and to validate their prognostic use. Methods and Results—: Patients prospectively enrolled in phase I of the CONFIRM registry (Coronary CT Angiography Evaluation for Clinical Outcomes) were included (derivation cohort: n=21, 132; 46% female) to develop CAD nomograms based on age–sex percentiles of segment involvement score (SIS) at each year of life (40–79 years). The relationship between SIS age–sex percentiles (SIS%) and MACE (all-cause death, myocardial infarction, unstable angina, and late revascularization) was tested in a nonoverlapping validation cohort (phase II, CONFIRM registry; n=3030, 44% female) by stratifying patients into 3 SIS% groups (⩽50th, 51–75th, and >75th) and comparing annualized MACE rates and time to MACE using multivariable Cox proportional hazards models adjusting for Framingham risk and chest pain typicality. Age–sex percentiles were well fitted to second-order polynomial curves (men: R 2 =0.86±0.12; women: R 2 =0.86±0.14). Using the nomograms, there were 1576, 965, and 489 patients, respectively, in the ⩽50th, 51–75th, and >75th SIS% groups. Annualized event rates were higher among patients with greater CAD burden (2.1% [95% confidence interval: 1.7%–2.7%], 3.9% [95% confidence interval: 3.0%–5.1%], and 7.2% [95% confidence interval: 5.4%–9.6%] in ⩽50th, 51–75th, and >75th SIS% groups, respectively; P <0.001). Adjusted MACE risk was significantly increased among patients in SIS% groups above the median compared with patients below the median (hazard ratio [95% confidence interval]: 1.9 [1.3–2.8] for 51–75th SIS% group and 3.4 [2.3–5.0] for >75th SIS% group; P <0.01 for both). Conclusions—: We have developed clinically pragmatic age- and sex-specific nomograms of CAD prevalence using coronary computed tomography angiography findings. Global plaque burden measured using SIS% is predictive of cardiac events independent of traditional risk assessment. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01443637. Abstract : Supplemental Digital Content is available in the text.